Pembuatan Rorak pada Perkebunan Kopi Arabica (Coffea arabica ) Untuk Meningkatkan Produktivitas - Muhammad Satibi; Nasamsir Nasamsir; Hayata Hayata (Jurnal Media Pertanian, 2019)
High rainfall and soil tillage without applying soil and water conservation techniques (WCT) have led to higher runoff and erosion and washed away top soil that is rich in nutrients needed by plants. This causes soil fertility to decrease over time. This study aims to examine the differences in growth and productivity of Arabica coffee that  the uses of rorak and without rorak. This research was conducted in the farmer's garden which is incorporated in the Barokah farmer group Sungai Jernih Village Gunung 7 District and Mekar Sari Village Kayu Aro District Kerinci Regency from May to July 2019. The experimental design used was unformatted trials and the location of the experiment was chosen intentionally (purposive) with the reason that in that area there are objects to be examined, namely coffee cultivation land that uses rorak and which does not use rorak. The treatment in this study was, Ro: land using rorak and R1: land without rorak. Vegetative and production variables observed included stem circumference (cm), leaf color, fruit weight with a sample of 100 chery coffees per tree (g) and soil variables including soil pH, soil moisture, nutrient content N, P, and K. The results of the study showed that making rorak produced differences in stem circumference, soil moisture content, nutrient content of N, P, K and soil pH as well as land productivity. Land using rorak yields 1047.61 kg / ha / year grenbeen and land without rorak 683.89 kg / ha / year grenbeen.Keywords: rorak, productivity of Arabica coffee